A Deficiency in Gamma Interferon or Interleukin-10 Modulates T-Cell-Dependent Responses to Heat Shock Protein 60 from Histoplasma capsulatum - Scheckelhoff, Mark (American Society for Microbiology, 2005)
Immunization of mice with heat shock protein 60 from Histoplasma capsulatum or a polypeptide from the protein designated F3 confers protection. Vβ8.1/8.2(+) T cells are critically important for the protective efficacy of this antigen. The production of interleukin-10 and gamma interferon following vaccination is essential for efficacy. In this study, we sought to determine whether the absence of either cytokine modified the repertoire of antigen-reactive T cells and whether it altered the functional properties of T cells. Mice lacking gamma interferon or interleukin-10 manifested a skewed repertoire compared to that of wild-type mice. The bias was most marked in gamma interferon-deficient mice and modestly altered in interleukin-10-deficient animals. The altered repertoire in gamma interferon-deficient mice could not be explained at the level of antigen presentation or by the absence of this population from mice. The proportion of T cells from interleukin-10-deficient mice manifesting a Th1 phenotype was greatly increased compared to that from wild-type animals. Transfer of splenocytes from gamma interferon- or interleukin-10-deficient mice immunized with heat shock protein 60 failed to confer protection in T-cell receptor α/β(−/−) mice. The transfer of T-cell clones that did not produce both cytokines failed to prolong survival in T-cell receptor α/β(−/−) mice, whereas the clones with the same features that were derived from wild-type mice did. These results indicate that the cytokine milieu influences the shape of the T-cell receptor repertoire and support the importance of gamma interferon and interleukin-10 in the efficacy of heat shock protein 60.